A Review on Smart Materials, Types and Modelling: Need of the Modern Era. (2021) - Gangele, Anshul; Mishra, Ajay
Abstract: The need for usage of smart materials/structures in modern perspective in industries and societal applications at large, cannot be overemphasized as with regard to the propertied i.e. durability, cost reductions and performance consistency. Smart materials are now days being used in all spheres of human life and technology. Smart materials also termed as intelligent materials or active materials include matrix of material systems possessing predominantly a set of properties as per their functional requirements. Some of the examples of smart materials are: Piezoelectric materials, Shape memory alloys, Magnetostrictive materials, Electro-rheological materials, Magneto-rheological fluids, electro- and magneto theological fluids, Thermoresponsive and Electrochromic material. This paper highlights the different types of smart materials and their applications.